2022
DOI: 10.1186/s13048-022-01080-3
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin alleviates cyclophosphamide-induced premature ovarian insufficiency in mice by reducing mitochondrial oxidative stress and pyroptosis in granulosa cells

Abstract: Background Exposure to cyclophosphamide (CTX) induces premature ovarian insufficiency (POI). Quercetin is a natural flavonoid that exhibits anti-inflammatory and antioxidant properties, and its antioxidant activity is correlated with POI. However, the mechanism underlying its protective role in CTX-induced ovarian dysfunction is unclear. This study aimed to explore whether quercetin can protect ovarian reserves by activating mitochondrial biogenesis and inhibiting pyroptosis. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…[31] Quercetin may also protect ovarian function by decreasing oxidative activity. [32,33] Kaempferol is a natural flavonoid from plants that is involved in several bioprocesses and has antioxidant, anti-inflammatory, and anticancer activities. [34] Kaempferol can promote sheep primordial follicle activation and induces sheep-growing follicle development via the PI3K/AKT pathway.…”
Section: Resultsmentioning
confidence: 99%
“…[31] Quercetin may also protect ovarian function by decreasing oxidative activity. [32,33] Kaempferol is a natural flavonoid from plants that is involved in several bioprocesses and has antioxidant, anti-inflammatory, and anticancer activities. [34] Kaempferol can promote sheep primordial follicle activation and induces sheep-growing follicle development via the PI3K/AKT pathway.…”
Section: Resultsmentioning
confidence: 99%
“…[ 67 ] Supporting this concept, studies have found that the GCs of women with POI exhibit elevated NLRP3, Caspase‐1, and IL‐1β levels. [ 19,68 ] Furthermore, the NLRP3 inflammasome is considered to be a key regulator of cellular inflammation, [ 67 ] and the expression levels of NLRP3, ASC, GSDMD, and Caspase‐1 mRNA and protein are increased, and the levels of IL‐18 and IL‐1β in serum and ovary are also raised in POI rats. [ 69 ] In line with these research findings, our study further validates the underlying connection between pyroptosis and POI.…”
Section: Discussionmentioning
confidence: 99%
“…[ 65,66 ] Specially, research has demonstrated a tight relationship between the NLRP3‐mediated pyroptosis and POI. [ 67 ] Supporting this concept, studies have found that the GCs of women with POI exhibit elevated NLRP3, Caspase‐1, and IL‐1β levels. [ 19,68 ] Furthermore, the NLRP3 inflammasome is considered to be a key regulator of cellular inflammation, [ 67 ] and the expression levels of NLRP3, ASC, GSDMD, and Caspase‐1 mRNA and protein are increased, and the levels of IL‐18 and IL‐1β in serum and ovary are also raised in POI rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular regulated protein kinase (ERK) (Guo et al., 2020) is the main member of the mitogen‐activated protein kinase family, which mainly regulates apoptosis, proliferation, and differentiation (Karisch et al., 2011). Phosphatase 1 (SHP‐1, also known as PTPN6) containing the Src homologous region 2 (SH2) domain is a non‐receptor protein tyrosine phosphatase (PTP) (Xu et al., 2012), a tyrosine phosphatase expressed in hematopoietic cells (Chen et al., 2022), containing two structures of SH2, the SHP‐1 gene is located in the p12–p13 region of chromosome 12, and the expressed product SHP‐1 is composed of 641 amino acid residues with a molecular weight of 70,510 Da, It plays an important role in cell signaling (Keranmu et al., 2022). Protein tyrosine phosphatase 1B (PTP1B) can bind directly to protein tyrosine kinase receptors, including IRs and epidermal growth factor receptors.…”
Section: Introductionmentioning
confidence: 99%